Pengetahuan Masyarakat Terhadap Keputusan Untuk Menjadi Nasabah di Bank Syariah - Andro Agil Nur Rakhmad; Selvi Kurniawati; Elif Pardiansyah (FEB Universitas Sultan Ageng Tirtayasa, 2021)
This study aims to analyze how literacy on Islamic banking affects the decisions to become the customers of Islamic banks. The method applied in this research is a qualitative method with a dynamic social approach and used descriptive analysis techniques. By collecting as much data as possible, compiling it, then analyzing and explaining the existing phenomena as deeply and truly as possible. Data collection was conducted by exploring a literature study, namely by reading, observing and analyzing some references or literature that have existed before and related to the influence of people knowledge on the decision to become Islamic bank customers. The result of this research is that the level of knowledge can affect the individual in making a decision to become customers in Islamic bank. Factors that affect their knowledge can come from education, media or information, environment, experience and age. These factors have also been proven to influence a person's decision to become a customer in Islamic banks.